Integrating Pentatonic Angklung into Physics Experiment to Identify Multiple Representation Skills in Junior High School - Rahmat, Anggi Datiatur; Kuswanto, Heru; Wilujeng, Insih (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2023)
Angklung is a traditional musical instrument from West Java that can be used as a learning medium for sound concepts. The study focuses on pentatonic Angklung as a musical instrument commonly used in Ngaseuk ceremonies as rice planting rituals in the Baduy tribe. This study aims to report the integration of pentatonic Angklung into physics experiments and investigate multiple representation skills. Technology-based mobile used as an experimental tool is Phypox. The designed activity aims to identify multiple representation skills using guided-inquiry models in four stages: Open, Explore, Create, and Share. The study participants are 31 8th-grade students at one of the junior high schools in West Java Province, Indonesia. Experiment activities investigate variables that affect the frequency of the pentatonic Angklung. A worksheet guides experiment activities following the syntax of the guided-inquiry model. The study results show that students use different representations at each stage in the worksheet. Students use four representations in this experimental activity: verbal, mathematical, pictorial, and graphical. It can be concluded that integrating pentatonic Angklung into physics experiments can identify students' multiple representation skills in junior high school.